Trouble déficitaire de l’attention à l’université - France Landry; Georgette Goupil (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents a descriptive portrait of Attention Deficit Hyperactivity Disorder (ADHD) in adults, more particularly in university students. After describing ADHD, we will look at the many challenges those students may encounter during their university studies. Moreover, we will present a tutoring program that is currently taking place at the University of Québec in Montréal (UQAM).